Biocompatibility of denture base acrylic resins evaluated M culture of L929 cells. Effect of polymerisation cycle and postpoymerisation treatments - Jorge, Janaina Habib [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP]; Pavarina, Ana Claudia [UNESP]; Carios, Iracilda Zeppone [UNESP] (Blackwell Publishing, 2007)
Objective: the purpose of this study was to evaluate the effect of two post-polymerisation treatments and different cycles of polymerisation on the cytotoxicity of two denture base resins.Materials and methods: the resins tested were Lucitone 550 and QC 20. Discs of resins were fabricated following the manufacturer's instructions. Lucitone 550 was processed by long cycle or short cycle. The resin QC 20 was processed by reverse cycle or normal cycle. The specimens were divided into groups: (i) post-polymerised in microwave for 3 min at 500 W; (ii) post-polymerised in water-bath at 55 degrees C for 60 min and (iii) without post-polymerisation. Eluates were prepared by placing three discs into a sterile glass vial with 9 ml of Eagle's medium and incubated at 37 degrees C for 24 hours. L929 cells were seeded into 96 3 well culture plates and DNA synthesis was assessed by H-thymidine incorporation assay.Results: the results were submitted to two-way ANOVA and Tukey HSD test. QC 20 specimens polymerised by the normal cycle and submitted to microwave post-polymerisation were graded as moderately cytotoxic. Similar results were observed for Lucitone 550 processed by long cycle without post-polymerisation. The other experimental groups were graded as not cytotoxic. After water-bath post-polymerisation, specimens of Lucitone 550 processed by long cycle produced significantly lower inhibition of DNA synthesis than the other groups.Conclusion: the long cycle increased the cytotoxicity of Lucitone 550 and water-bath post-polymerisation reduced the cytotoxicity of Lucitone 550 processed by long cycle.
Keywords: cytotoxicity; acrylic resin; polymerisation cycle; cell culture